1965
DOI: 10.1017/s0022112065000241
|View full text |Cite
|
Sign up to set email alerts
|

Transition in circular Couette flow

Abstract: Two distinct kinds of transition have been identified in Couette flow between concentric rotating cylinders. The first, which will be called transition by spectral evolution, is characteristic of the motion when the inner cylinder has a larger angular velocity than the outer one. As the speed increases, a succession of secondary modes is excited; the first is the Taylor motion (periodic in the axial direction), and the second is a pattern of travelling waves (periodic in the circumferential direction). Higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
658
1
5

Year Published

1971
1971
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,017 publications
(719 citation statements)
references
References 8 publications
45
658
1
5
Order By: Relevance
“…8,9 The sudden appearance of localised turbulent patches in an otherwise quiescent flow was first observed by Osborne Reynolds for pipe flow 1 and has since been found to be the starting point of turbulence in most shear flows. 2,4,[10][11][12][13][14][15] Curiously, in this regime it is impossible to maintain turbulence over extended regions as it automatically 16,17 reduces to patches of characteristic size, called puffs in pipe flow (see Fig. 1a).…”
Section: Oct 2015mentioning
confidence: 99%
“…8,9 The sudden appearance of localised turbulent patches in an otherwise quiescent flow was first observed by Osborne Reynolds for pipe flow 1 and has since been found to be the starting point of turbulence in most shear flows. 2,4,[10][11][12][13][14][15] Curiously, in this regime it is impossible to maintain turbulence over extended regions as it automatically 16,17 reduces to patches of characteristic size, called puffs in pipe flow (see Fig. 1a).…”
Section: Oct 2015mentioning
confidence: 99%
“…The H 1 and H 2 bulleted curves shown in Fig. 2c correspond to experimental hysteretic SPT boundaries when decreasing R i from above in [2] and [1], respectively. In particular, we found …”
Section: Intermittent Regimes From Nonmodal Instabilitiesmentioning
confidence: 79%
“…This has been done for values of R i and R o for which experiments reported laminar-turbulent spiral coherence, also termed as spiral turbulence [2,5,4]. Numerical simulation with moderate resolution have managed to reproduce such a flow (see Fig.…”
Section: Intermittent Regimes From Nonmodal Instabilitiesmentioning
confidence: 99%
“…Similarly, Coles (1965) in a Couette flow study found that the transition to turbulence occurred at a higher Rossby number than that at whi ch it woul d di sappear when condi tions were reversed. Since a finite amplitude disturbance can exist and be unstable in a flow Reynolds number less than the initial value for production of infinitesimal disturbances, the present hysteresis results are explainable.…”
Section: Spectra DI Storti On and Hys Teres Ismentioning
confidence: 84%